Influence of miscut direction on magnetic anisotropy of magnetite films grown on vicinal MgO (100) - SHVETS, IGOR; ARORA, SUNIL; RAMOS, RAFAEL (American Institute of Physics, 2010)
Ferromagnetic resonance (FMR) was used to study the influence of miscut direction on the in-plane fourfold and uniaxial magnetic anisotropies of epitaxial Fe3O4 films grown on vicinal MgO (100) surfaces. In-plane angular dependent measurements at room temperature on Fe3O4 films on two different miscut directions (miscut along < 011 > and < 010 > directions) of MgO showed the presence of both in-plane fourfold (cubic) and in-plane uniaxial anisotropies. Temperature dependent FMR investigations show that the in-plane fourfold anisotropy constant (K-4) is approximately the same for both samples at room temperature. The magnitude of K-4 increases gradually with decreasing temperature and changes sign from negative to positive values at 130 K. This behavior is consistent with that of bulk magnetite. In addition to K-4, we find an additional uniaxial component (K-2), whose strength is quite different for the different miscut directions. The magnitude of K-2 shows very little or no temperature dependence. The observed differences in the magnitude of K-2 with miscut directions are related to the changes in the antiphase boundary structure and altered magnetic configurations at the boundaries.
Journal of Applied Physics
11th Joint MMM-Intermag Conference
PUBLISHED
Washington DC, USA
Keywords: epitaxial; Fe films; surface; Ag (001); Nanoscience & Materials